Análisis de la política educativa de movilidad y acceso geográfico de los estudiantes del Distrito de Educación 13D07 Chone-Flavio Alfaro 2024-2025 - Soledispa Choez, Yureima Christel (2026)
This study analyzed the educational policy on student mobility and geographic access within the 13D07 Chone-Flavio Alfaro District during the 2024-2025 academic year, aiming to propose actions of improvement. The research employed inductive, deductive, and analytical-synthetic methods, alongside bibliographic and field investigation approaches. Data collection techniques included interviews and surveys. Among the main findings, it is outlined that the primary regulations governing mobility and geographic access are the Organic Law of Intercultural Education (2011) and the School Transportation Regulations for Educational Institutions within the National System of Education (2022). The policy assessment revealed that 34% of students perceive their educational institution as located in a hard-to-access area, while 26% report tardiness due to distance or lack of transportation. Additionally, 44% of students experienced difficulties getting transportation during peak demand times. Based on these results, a proposal for policy enhancement was developed.